KARAKTERISTIK DAN HASIL NITRIDISASI STAINLESS STEEL TIPE 316L DENGAN DAPUR FLUIDISED BED - Astana Widi, I Komang (JURNAL FLYWHEEL, 2008)
The investigation of 316L austenitic stainless steel with nitriding used laboratory scale of fluidized bed reactor has been done. Nitriding temperature treatment is 500 C with variable process as 1, 3 and 6 hours. Then, this investigation used matalography (Scanning Electron Microscope) showed that AISI 316L is formed nitride hard layer on the surface. This nitride hard layer as advanced of austenite as S phase. This layer is formed in one hour as less effective. The profile of hardnes value is showed that tend increase in longer time processing.